SHAREHOLDER VALUE CREATION IN POLAND. VALUE BUILDING AND ITS TRANSFER TO SHAREHOLDERS IN COMPANIES LISTED ON WARSAW STOCK EXCHANGE - Jarosław NOWICKI (Studia Universitatis Babeş-Bolyai Negotia, 2015)
The core research of the current paper is focused on the value-based management concept (VBM), which developed around the definition of the enterprise’s objective as shareholder value maximization or shareholder value creation. The study deals with the issue of performance measurement within the VBM concept and presents the findings of the research conducted on non-financial companies listed on Warsaw Stock Exchange. The results of the study show that the Warsaw Stock Exchange non-financial listed companies, in average, did not build value. This indicates that their returns on equity (ROE ratios) did not cover the cost of capital. Regarding the value transfer, the results indicate that this transfer took place, in average, only during 2013; for the 2011 and 2012 the total shareholder return generated by the respective companies was lower than expected. However, the results indicate a large diversity among the analyzed companies in terms of REP and CSV spread. Thus, in the end, the data indicates low correlation between the value building process and value transfer for 2011 and 2012, and a moderate correlation for 2013.